Efeito do tempo de estocagem sobre a composição bromatológica das fezes de galinhas poedeiras - Deoliveira, MDS; Vieira, PDF; Banzatto, D. A. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
In this trial the bromatologic composition of caged laying hen manure was studied according to a completely randomized design with four treatments and six replications. The treatments T-1, T-2, T-3 and T-4 consisted of caged laying hen manure stocked for 0; 7; 14 and 21-day times, respectively. Stocking period until 21 days decreased crude protein (P<0.01) and gross energy (P<0.01). The best bromatologic composition of hen caged manure data were proportional to the lower stocking time.

Por delineamento inteiramente casualizado com quatro tratamentos e seis repetições, realizou-se um ensaio com o intuito de estudar a composição bromatológica das fezes de galinhas poedeiras. Foram utilizados os tratamentos T1, T2, T3 e T4, correspondendo, respectivamente, aos tempos 0; 7; 14 e 21 dias de estocagem. Os resultados revelaram decréscimo linear (P < 0,01) nos teores de proteína bruta e de energia bruta de fezes de galinhas poedeiras. Quanto menor o tempo de estocagem, melhor foi a composição bromatológica de fezes de galinhas poedeiras.
Effect of stocking times on bromatologic composition of caged laying hen manure
Keywords: LAYING MANURE; HEN MANURE; BROMATOLOGIC DETERMINATION; LAYING HEN